Emotional reactivity to social stimuli in patients with eating disorders - Tapajoz Pereira de Sampaio, Fernanda (2015)
Patients with eating disorders often display a wide range of difficulties in psychosocial functioning. Most of the studies on this subject have focused on theory of mind; however, little is known about the subjective emotional reactivity of patients to social situations. The aim of this study was to evaluate the patients' perceptions of their own emotions when viewing pictures with social content. Emotional reactivity was assessed in 85 women (29 with anorexia nervosa, 28 with bulimia nervosa, and 28 healthy controls) by using 30 images from the International Affective Picture System. Images were divided into categories based on its social content and its emotional valence. The emotional response was evaluated through the Self-Assessment Manikin. Patients with bulimia nervosa presented higher arousal and lower control when viewing images with social content of pleasant, unpleasant, and neutral valence. Patients with anorexia nervosa reported higher arousal and lower control only for social images with neutral valence. There were no differences between groups for the control images. The finding of specific differences in emotional reactivity to pictures with social content contributes to a more accurate understanding of the difficulties of patients in social situations.